The Implementation of Self-Instruction and Reframing Group Counselling Techniques to Improve Students' Self-Confidence - Karamoy, Yurike Kinanthy; Wibowo, Mungin Eddy; Jafar, Muhammad (Jurnal Bimbingan Konseling, 2018)
This study aimed to examine the effectiveness of self-instruction and reframing group counselling techniques to improve students' self-confidence. Those techniques were done twice in each group counselling service. To cover up the implementation of the techniques, this study used randomized pretest-posttest comparison group design involving 14 students having low self-confidence chosen from 99 students by using purposive sampling technique. Once the data collection and data analysis were done, this study found that both self-instruction and reframing group counselling techniques have the same effectiveness in improving the self-confidence of the tenth grade students of Online Business and Marketing Department of State Vocational High School (SMK Negeri) 4 Jember. At last, the discussion of this paper is focused on examining the possibilities of the implementation of self-instruction and reframing group counselling techniques in SMK Negeri 4 Jember